Geckos in the granite: two new geckos (Squamata: Gekkonidae) from rocky, scrub habitats in Rishi Valley, Andhra Pradesh, India - Agarwal, Ishan; Thackeray, Tejas; Khandekar, Akshay (Zootaxa, 2020)
Two new species of geckos from the genera Cnemaspis and Hemidactylus are described from a granite outcrop in the Rishi Valley, Chittoor District, Andhra Pradesh, India. Cnemaspis rishivalleyensis sp. nov. and Hemidactylus rishivalleyensis sp. nov. are presently known only from their type locality and are 8.7 % and 10.9 % divergent from their closest known sister species, respectively. The new species are allied to the mysoriensis and murrayi clades of South Asian Cnemaspis and the brookii group of Indian Hemidactylus, respectively. The two new species can be diagnosed from regional congeners by the number and arrangement of femoral and precloacal pores and poreless scales separating these series, body size, the number of tubercles in paravertebral rows, the number of enlarged tubercles around mid-body, the number of ventral scales across mid-body, the number of lamellae beneath digit IV of pes and manus, and subtle differences in colour pattern. Four endemic geckos now have their type localities within 10 km of each other, Cnemaspis graniticola and Cyrtodactylus rishivalleyensis from Horsley Hills and the two new species from Rishi valley. The two new species are also the third endemic species each of Cnemaspis and Hemidactylus from Andhra Pradesh.